Efficacy of telemedical interventional management in patients with heart failure (TIM-HF2): a randomised, controlled, parallel-group, unmasked trial. Issue 10152 (22nd September 2018) - Koehler, Friedrich; Koehler, Kerstin; Deckwart, Oliver; Prescher, Sandra; Wegscheider, Karl; Kirwan, Bridget-Anne; Winkler, Sebastian; Vettorazzi, Eik; Bruch, Leonhard; Oeff, Michael; Zugck, Christian; Doerr, Gesine; et al.
Summary: Background: Remote patient management in patients with heart failure might help to detect early signs and symptoms of cardiac decompensation, thus enabling a prompt initiation of the appropriate treatment and care before a full manifestation of a heart failure decompensation. We aimed to investigate the efficacy of our remote patient management intervention on mortality and morbidity in a well defined heart failure population. Methods: The Telemedical Interventional Management in Heart Failure II (TIM-HF2) trial was a prospective, randomised, controlled, parallel-group, unmasked (with randomisation concealment), multicentre trial with pragmatic elements introduced for data collection. The trial was done in Germany, and patients were recruited from hospitals and cardiology practices. Eligible patients had heart failure, were in New York Heart Association class II or III, had been admitted to hospital for heart failure within 12 months before randomisation, and had a left ventricular ejection fraction (LVEF) of 45% or lower (or if higher than 45%, oral diuretics were being prescribed). Patients with major depression were excluded. Patients were randomly assigned (1:1) using a secure web-based system to either remote patient management plus usual care or to usual care only and were followed up for a maximum of 393 days. The primary outcome was percentage of days lost due to unplanned cardiovascular hospital admissions or all-cause death, analysed in the full analysis set. Key secondary outcomes were all-cause and cardiovascular mortality. This study is registered withClinicalTrials.gov, numberNCT01878630, and has now been completed. Findings: Between Aug 13, 2013, and May 12, 2017, 1571 patients were randomly assigned to remote patient management (n=796) or usual care (n=775). Of these 1571 patients, 765 in the remote patient management group and 773 in the usual care group started their assigned care, and were included in the full analysis set. The percentage of days lost due to unplanned cardiovascular hospital admissions and all-cause death was 4·88% (95% CI 4·55–5·23) in the remote patient management group and 6·64% (6·19–7·13) in the usual care group (ratio 0·80, 95% CI 0·65–1·00; p=0·0460). Patients assigned to remote patient management lost a mean of 17·8 days (95% CI 16·6–19·1) per year compared with 24·2 days (22·6–26·0) per year for patients assigned to usual care. The all-cause death rate was 7·86 (95% CI 6·14–10·10) per 100 person-years of follow-up in the remote patient management group compared with 11·34 (9·21–13·95) per 100 person-years of follow-up in the usual care group (hazard ratio [HR] 0·70, 95% CI 0·50–0·96; p=0·0280). Cardiovascular mortality was not significantly different between the two groups (HR 0·671, 95% CI 0·45–1·01; p=0·0560). Interpretation: The TIM-HF2 trial suggests that a structured remote patient management intervention, when used in a well defined heart failure population, could reduce the percentage of days lost due to unplanned cardiovascular hospital admissions and all-cause mortality. Funding: German Federal Ministry of Education and Research.